Antimicrobial Action and Reversal of Resistance in MRSA by Difluorobenzamide Derivatives Targeted at FtsZ - Wern Chern Chai; Jonathan J. Whittall; Di Song; Steven W. Polyak; Abiodun D. Ogunniyi; Yinhu Wang; Fangchao Bi; Shutao Ma; Susan J. Semple; Henrietta Venter (Antibiotics, 2020)
The bacterial cell division protein, FtsZ, has been identified as a target for antimicrobial development. Derivatives of 3-methoxybenzamide have shown promising activities as FtsZ inhibitors in Gram-positive bacteria. We sought to characterise the activity of five difluorobenzamide derivatives with non-heterocyclic substituents attached through the 3-oxygen. These compounds exhibited antimicrobial activity against methicillin resistant Staphylococcus aureus (MRSA), with an isopentyloxy-substituted compound showing modest activity against vancomycin resistant Enterococcus faecium (VRE). The compounds were able to reverse resistance to oxacillin in highly resistant clinical MRSA strains at concentrations far below their MICs. Three of the compounds inhibited an Escherichia coli strain lacking the AcrAB components of a drug efflux pump, which suggests the lack of Gram-negative activity can partly be attributed to efflux. The compounds inhibited cell division by targeting S. aureus FtsZ, producing a dose-dependent increase in GTPase rate which increased the rate of FtsZ polymerization and stabilized the FtsZ polymers. These compounds did not affect the polymerization of mammalian tubulin and did not display haemolytic activity or cytotoxicity. These derivatives are therefore promising compounds for further development as antimicrobial agents or as resistance breakers to re-sensitive MRSA to beta-lactam antibiotics.